2011
DOI: 10.1099/jmm.0.024729-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a line probe assay for the rapid detection of gyrA mutations associated with fluoroquinolone resistance in multidrug-resistant Mycobacterium tuberculosis

Abstract: The aim of this study was to establish the importance of detecting fluoroquinolone (FQ) resistance in multidrug resistant (MDR) Mycobacterium tuberculosis, and to show the usefulness of a hybridization-based line probe assay (LiPA) for detecting gyrA mutations. Thirty-three MDR M. tuberculosis isolates were collected from a total of sixty MDR isolates identified in Japan over 6 months during a national surveillance study in 2002. Seventeen MDR isolates were collected by the National Center for Global Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…It is also important to detect resistance to PZA and LVX in MDR tuberculosis, as the majority of MDR M. tuberculosis isolates have been reported to be resistant to either PZA or LVX in Japan (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to detect resistance to PZA and LVX in MDR tuberculosis, as the majority of MDR M. tuberculosis isolates have been reported to be resistant to either PZA or LVX in Japan (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations imposed by the low growth rate of MTBC, genotypic antibiotic susceptibility tests have been introduced and either have been endorsed by the World Health Organization or are currently under evaluation (11,72,73,98,119,144). Given that these hybridization-based assays interrogate the DNA rather than the amino acid sequence, they detect both synonymous and nonsynonymous mutations, unless the genetic diversity in the target regions was taken into consideration for the design of the respective probes (4,12,24,83,155). For example, additional probes had to be included for the assay manufactured by Nipro Corp. to cover several neutral or silent mutations in pncA (13,108,144).…”
Section: Known Impact Of Genetic Diversitymentioning
confidence: 99%
“…Attempts have also been made to correlate the nature and kind of gyrA mutations with the level of resistance to FQs in M. tuberculosis strains with conflicting results. Some studies have reported that M. tuberculosis strains containing D94G mutation in the gyrA gene exhibit high-level resistance to FQs while those with D94A mutation have lower MIC for LFX [93,96,97]. On the contrary, other reports have not found an association of different mutation patterns in gyrA or gyrB genes with the level of FQ resistance in M. tuberculosis isolates [89,94].…”
Section: Mechanism Of Action and Resistance Of Fluoroquinolones In Mmentioning
confidence: 69%
“…The presence of missense mutations in the so-called quinolone resistance-determining region (QRDR) of gyrA or gyrB genes conferring resistance to FQs was subsequently confirmed by using clinical M. tuberculosis isolates in multiple studies [83][84][85][87][88][89][90][91][92][93][94][95][96][97]. The presence of S95 or T95 at gyrA codon 95 is a naturally occurring polymorphism that is not associated with resistance of M. tuberculosis isolates to FQs.…”
Section: Mechanism Of Action and Resistance Of Fluoroquinolones In Mmentioning
confidence: 99%
See 1 more Smart Citation